Performance Testing On Mixture Of Kisamir Pure Plant Oil (Ppo) And Kerosene As Wick Stove Fuel - Emi Yuliarita (Testing Center for Oil and Gas LEMIGAS, 2010)
Pure Plant Oil (PPO) which is made from â€œkisamirâ€ seed has smaller kinetic viscosity value than jatropha and coconut oil. So it has potential to be used as alternative fuel/mixed kerosene. The test result of some main physical/chemical characteristics of fuel made from kerosine and pure plant oil (5% to 20% volume) are still in the limit of kerosene specification as decided by the government. However, the maximum power test result of the mixture of PPO and kerosene that has been tested on 16 wicks stove shows that the higher content of PPO in kerosene will decrease the maximum stove performance as well as stoveâ€™s efficiency value. But the blue color of fire gets clearer, because of less amount of sulfur by adding PPO in kerosene. The use of PPO up to 20% will reduce sulphur content up to 20%.